Supply Chain Resilience in Era of combined effects of COVID-19, Brexit, and Russia-Ukraine war: Global Trends and Developments - Johannes LITZENBURGER; Nicole MAU; Markus MAU (Communications of International Proceedings, 2022)
The subject of consideration in the article is the issue of using social entrepreneurship in the organization of a comprehensive reintegration system. Such an approach to the subject causes the analysis will concern social entrepreneurship in the form of entrepreneurial activities undertaken to achieve a social goal. In other words, it is about solving social problems in the spirit of entrepreneurship and innovation, with the acceptance of risk and market rules and solutions. The analysis of documents and other existing sources was used to study these phenomena. The conducted research proves that the inclusion of social enterprises in activities in the field of reintegration is, on the one hand, a necessity, and on the other hand, it is also an opportunity to recreate pro-social behaviour patterns among citizens, which will contribute to meeting the expectations of people covered by this type of activity.
Keywords: social economy; social entrepreneurship; social enterprises; reintegration; foundation